ANALISIS STRATEGI DAN DAYA SAING MASKAPAI BERBIAYA RENDAH : STUDY KASUS RYANAIR Ltd - Fino Wahyudi Abdul; Eko Joyoprayitno; Taufan Maulamin (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
Before the emergence of flying at low cost, large companies such as British Airways has dominated the European aviation industry services company. When the current industry trends undergo strict regulations in the European Union in 1997, where an airline from one member state can not fly in one market domestic that different countries, but Ryanair Ltd., dared to enter the aviation industry with the major obstacle. They were able to break through the market with low cost operations while maintaining the advantages, distinguishes itself with a permanent service implements to customers who are superior, and achieve cost savings through the use services to the Internet network.As a result of its strategy Market Busting, Ryanair Ltd., has become the largest low - cost airlines (one of the flight operators) in Europe. For the fiscal year 2004, the company brings in revenue of 1.32 billion, increased 44% from the year previous. Ryanair Ltd. currently provides service to 93 cities across Europe, recorded more than 15 million passengers per year.This paper analyzes the strategy and competitiveness Ryanair Ltd. to achieve success using SWOT analysis and Business Model Canvas (BMC). Where the use of SWOT analysis tool and the BMC is expected to displays a simpler business model.